Tuberculosis and air travel: a systematic review and analysis of policy - Abubakar, Ibrahim (The Lancet infectious diseases, 2010)
WHO international guidelines for the control of tuberculosis in relation to air travel require—after a risk assessment—tracing of passengers who sat for longer than 8 h in rows adjacent to people with pulmonary tuberculosis who are smear positive or smear negative. A further recommendation is that all commercial air travel should be prohibited until the person has two consecutive negative sputum smears for drug-susceptible tuberculosis or two consecutive cultures for multidrug-resistant tuberculosis. In this Review I examine the evidence put forward to support these recommendations and assess whether such an approach is justifiable. A systematic review identified 39 studies of which 13 were included. The majority of studies found no evidence of transmission. Only two studies reported reliable evidence of transmission. The analysis suggests that there is reason to doubt the value of actively screening air passengers for infection with Mycobacterium tuberculosis and that the resources used might be better spent addressing other priorities for the control of tuberculosis.